Megacity governance in South Asia : a comparative study - Siddiqui, Kamal (Dhaka : University Press, 2004)
On urban planning and disarray in three cities in India, one in Bangladesh, and one in Pakistan; contributed study.
Includes bibliographical references (pages [483]-499) and index.
BIED
Complimentary copy from BIED, Donated By Akbar Ali Khan
Keywords: City planning -- India; City planning -- Bangladesh; City planning -- Pakistan; Social science